A study on the relationship between emotional intelligence and quality of work life at Pejabat Tanah Dan Jajahan Tumpat, Kelantan / Salwani Yaacob - Yaacob, Salwani (Faculty of Business and Management, 2019)
The aim of this study is to investigate the relationship between emotional intelligence and the quality of work life. The researcher has used four factors of emotional intelligence consist of self-awareness, self-management, social-awareness and relationship management. The researcher has used a correlation study which to found out the relationship between two variables. The factors of emotional intelligence can give a positive or negative significant relationship towards the quality of work life. The emotional intelligence of one's person can give effect to their quality of working life. It has shown how important emotional intelligence and organization have been facing some consequences if their employees lack emotional intelligence. The study is to findings the four factors of emotional intelligence among employees'. The objective of conducting this study is to study which the highest and the lowest part among the four factors of emotional intelligence. The study was conducted in order to determine if there was a relationship between emotional intelligence and the quality of work life. The researcher has conducted research at the Pejabat Tanah dan Jajahan Tumpat at Kelantan. There were consisted of three selected department of the organization. The selected respondents' of three departments is the real estate department, administration department, and development department. The questionnaires were distributed to the entire selected department. A result finding is based on the collected data that have been analyzed by using the Statistical Package in the Social Sciences Software (SPSS). This study can create a positive emotional climate for the respondents' workplace and personal life.